Thinking with Faith, Thinking as Faith What Comes After Onto-theo-logy? - Caputo, John D. 1940- (2022)
Despite Heidegger’s constant claims to the contrary, thinking is not opposed to faith. Indeed, against his own intentions, Heidegger’s critique of onto-theo-logy, which breaks the grip of modernity, issues in a faith more radically conceived. This faith is the thinking, this thinking is the faith that becomes possible in the post-secular space which Heidegger’s critique of modernity opens. Although the great medieval theologians like Augustine and Aquinas are not onto-theo-logians in a strict sense, they, along with the whole history of metaphysics, fall under its wider sense of any centered and foundational discourse. But any discourse that eludes onto-theo-logy in the wider sense finds itself embracing a faith, not reducible to belief, where thinking is a form of faith and faith is a form of thinking. Derrida’s "Circumfession," a paradigmatic post-ontotheological discourse, is a work of prayer and a confession of faith in the open-endedness of the event, an un-programmable future ( à venir ). This text communicates with Heidegger thinking the "open," the "promise" of language, of the Zukunft embedded in the Herkunft , constituting the "piety of thinking."
Keywords: Aquinas; Augustine; Derrida; Heidegger; Marion; Faith; onto-theo-logy; Prayer; Thinking